Evaluation and Management of Alcohol use Disorder among Older Adults - Joshi, Pallavi (Curr Geriatr Rep, 2021)
PURPOSE OF REVIEW: The prevalence of alcohol use disorder (AUD) among older adults in the United States is rising, but remains underdiagnosed, underreported, and inadequately managed. This review highlights the medical, social, and cultural factors of AUD in older adults and provides guidelines for its screening, evaluation, and management. RECENT FINDINGS: The COVID-19 pandemic has created additional challenges and barriers to care, as older adults may have disproportionate worsening of anxiety, depression, and substance use resulting from increased isolation related to physical distancing and shelter-in-place guidelines. SUMMARY: All older adults should be routinely screened for AUD with standardized screening tools. If a patient’s screening results are positive, a clinician should conduct a brief assessment, which may be supplemented by laboratory tests. Most older adults at risk for alcohol misuse do not need specialized SUD treatment, but most can benefit from Screening, Brief Intervention, and Referral to Treatment (SBIRT) to prevent substance misuse before it occurs. Medications for the treatment of AUD in older adults include naltrexone, acamprosate, disulfiram, gabapentin and topiramate. Psychosocial treatments, including mutual help groups, are equally important.